The Estimation of Potential Carbon Tax Revenue Through A Cap and Tax Scheme on Coal-Fired Power Plants in Indonesia - Giacinta Betralda Anin Pradita; Wuri Handayani (The Indonesian Journal of Accounting Research, 2026)
This study aims to estimate potential carbon tax revenue using the cap-and-tax method applied to coal-fired power plants. After estimating the value, it will be analysed to inform allocation strategies through earmarking policies. The cap-and-tax method is considered a unique solution because it combines the advantages of a carbon tax and an ETS. This study employs a qualitative case study approach to analyse quantitative data from six coal-fired power plants with a capacity greater than 400 MW to calculate the total potential carbon tax revenue. The results of this study show that the potential value of carbon tax revenue is still lower than the estimated funding needs calculated by the International Monetary Fund (IMF) of 3500 trillion, as well as lower than some previous studies, totaling IDR 117 billion for 2021 compared to Pratama et al (2021) which reported IDR 20.56 trillion in the same year due to focused only one energy subsector. This revenue is then allocated through earmarking policy, applying the OECD percentage with adjustments from the climate budget tagging (CBT) policy. This finding confirms that if the government can maximise tax collection, the amount obtained will be sufficient to meet the estimated funding needs calculated by the IMF.